PROMOTING THE PURCHASING OF PERFORMANCE TESTED DORPER RAMS: THE ROLE OF AGRICULTURAL EXTENSION - Fourie, P.J. (South African Journal of Agricultural Extension, 2015)
The sale price of 868 Dorper rams sold between 2004 and 2013 were compared with their measured performances. The independent variables (Selection, Weaning Index, Wean direct, Wean maternal, Post wean, Breeding value for number of lambs weaned (GLS), Relative economic value (REV), Selection Index percentage (SI%), Scrotal deviation (SD), Mean Lamb Index (MLI) and Ewe productivity Index (EPI) were used to predict the dependent variable (sale price of the Dorper rams) from 2004 to 2013. Factors with the most significant influence in order of importance were selection (stud or commercial), SI% and REV. It is evident that rams with better performance figures fetched higher prices. Although buyers did consider breeding values when buying rams none of it consistently contributed to sale price. It appears that buyers rather responded on SI%, a performance parameter familiar to them which was displayed in the sale catalogue from the beginning of the project. In an extension approach performance data must form the base for convincing breeders and farmers to move towards more scientific breeding methods, combining visual evaluation with measured performance at all Dorper sales. A unified effort by research, extension and the Breeders’ Society may address the problem best.
Published Article
Keywords: Dorper veld-ram clubs; performance measurements; Sale Price; Agricultural extension